A facile one-step flash combustion synthesis and characterization on C doped NiO nanostructures. (September 2019) - Shkir, Mohd; Arif, Mohd; Singh, Arun; Yahia, I.S.; Algarni, H.; AlFaify, S.
Abstract: Synthesis of NiO nanostructures in presence of different concentrations of citric acid (CA) was achieved through flash combustion technique. The NiO nanostructures formation was confirmed through X-ray diffraction analysis. At low concentrations of CA no extra peak was observed in XRD patterns, however when the CA concentration was raised to 5 and 10 g, two new extra peaks appeared at 44.6° and 51.9° which may be attributed to the presence of C. The crystallite size was noticed to reduce from 29 to 18 nm with increase in the CA concentration. All observed Raman bands were noticed to be shifted owing to the quantum size effect. EDX and SEM mapping confirm the existence of C. SEM images confirm the cubic nanocrystalline morphology for 0.5 g CA:NiO, however with increasing CA concentration a drastic change in morphology, i.e. from nanocrystals to extended nanosheets, was observed. The energy gap values were determined using Kubelka-Munk theory and found in range of 3.5–4.0 eV. An additional energy gap ∼2 eV was also noticed at higher CA concentration. The values of relative permittivity, ε r ′, were found in the range of 18–110 for CA concentration upto 5g, however, at 10.0 g CA its value was found to be order of 10 4 at 2 × 10 5  Hz.